THE EFFECT OF NURSE KNOWLEDGE ON THE IMPLEMENTATION OF STANDARD OPERATIONAL PAIN MANAGEMENT PROCEDURES IN SRI PAMELA TEBING HIGH HOSPITAL IN 2022 - Kamaliah Ainun (Institute of Computer Science (IOCS), 2022)
Nurses as one of the health workers in hospitals play an important role in achieving health development goals. the success of health services and the participation of nurses in providing appropriate nursing care for patients. One of the efforts to maintain patient safety is to apply SOP (Standard Operating Procedure). The purpose of this study was to determine the effect of nurses on the implementation of pain management operational procedures at Sri Pamela Tebing Tinggi Hospital in 2022. The type of research used was descriptive, namely describing an objective situation and examining between two variables in a situation or group of subjects. This is used to see the effect of other symptoms or one variable with another variable. The results of the study show the majority based on table 4.2. it can be seen that from 25 respondents, 8 respondents (32.0%) have good knowledge, 11 respondents (44.0%) have sufficient knowledge and then 6 respondents (24.0%) have less knowledge. applying SOP (Standard Operating Procedure) in every action taken by the main nurse is sufficient. Based on the results of this study, nurses are expected to maintain patient safety by implementing SOPs (Standard Operating Procedures) in every action taken by nurses, where nurses need greater knowledge about the importance of hospital management so that the services provided can provide satisfaction to patients.